Challenges of Car Industry in Dealing with Social Media Marketing Tools - Mohammad Muqtader Yousafzai (International Journal of Engineering and Management Research, 2023)
With the introduction of social media platforms, marketing methods in the car industry have undergone a fundamental shift. This study explores the difficulties the auto sector has in using social media marketing tools to improve brand visibility, interact with customers, and traverses the ever-changing digital landscape. Given the continued influence of social media on customer preferences, it is critical to comprehend the difficulties faced by the automotive industry to maintain competitiveness and long-term growth. The study takes a multipronged approach, combining qualitative and quantitative analysis to investigate the intricacies involved in the incorporation of social media into automakers' marketing campaigns. Additionally, issues related to privacy concerns, data security, and the management of customer feedback on various platforms poses substantial hurdles for the industry. Furthermore, the study investigates the impact of social media on consumer behavior and decision-making processes within the automotive purchase journey. By examining case studies and industry practices, this research aims to provide valuable insights and recommendations for car manufacturers to overcome these challenges, optimize their social media marketing efforts, and leverage the potential of these platforms to foster brand loyalty and customer satisfaction. Ultimately, the findings of this research contribute to the evolving discourse on the intersection of the automotive industry and social media marketing, offering practical solutions and strategic recommendations to empower car manufacturers in navigating the intricacies of the digital age.